The general anti‐avoidance rule - Cowx, Mary; Kerr, Jon N. (Contemporary Accounting Research, 2024)
Abstract The general anti‐avoidance rule, or GAAR, is an enforcement mechanism that gives a country's taxing authority broad power to deny a taxpayer tax benefits associated with any transaction. Although GAARs are becoming increasingly common, the presence of a GAAR is generally overlooked by researchers and thus has been left unstudied. In this paper, we provide an initial investigation by studying the effect of GAARs on firm‐level corporate tax avoidance behaviors. Using an indicator for the enactment or strengthening of a GAAR within a country in a stacked difference‐in‐differences design, we find GAAR enactment is associated with a statistically and economically significant decrease in firm‐level tax avoidance. Additional cross‐sectional analyses show that the decline in tax avoidance occurs for conventional GAARs and economic substance‐type rules, original and strengthened GAARs, and domestic and multinational firms. Results also show that the effect is strongest for firms with higher levels of pre‐GAAR‐enactment tax avoidance and for firms incorporated in countries where the burden of proof lies with the taxpayer.